Masalah Sosial Masyarakat Indonesia yang Diangkat dalam Novel Ayah dan Sirkus Pohon Karya Andrea Hirata - Ramadhani, Nur Fadhilah Rizqi (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research is entitled "Social Problems in Indonesian Society Raised in the Novel Ayah dan Sirkus Pohon by Andrea Hirata." The formulation of the research problem is what social problems in Indonesia are represented in the Novel Ayah dan Sirkus Pohon. This research aims to describe and analyze the social problems that exist in Indonesian society, as described in the novel. This research is a qualitative descriptive study using a literary of sociology and social problem theory. The data collection techniques used were note-taking and a literature study. The results of this research revealed several social problems found in Indonesian society that were touched upon in the novel, such as divorce, educational problems, and poverty.